2020
DOI: 10.1016/j.omtm.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-Derived Intestinal Organoids from Cystic Fibrosis Patients Acquire CFTR Activity upon TALEN-Mediated Repair of the p.F508del Mutation

Abstract: Cystic fibrosis (CF) is the main genetic cause of death among the Caucasian population. The disease is characterized by abnormal fluid and electrolyte mobility across secretory epithelia. The first manifestations occur within hours of birth (meconium ileus), later extending to other organs, generally affecting the respiratory tract. It is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. CFTR encodes a cyclic adenosine monophosphate (cAMP)-dependent, phosphorylation-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Induced pluripotent stem cell (iPSC) technologies and patient-derived iPSCs provide opportunities for regenerative medicine, drug discovery, and disease modeling from patient-derived stem cells, such as in cystic fibrosis, Huntington’s, Duchenne muscular dystrophy, Alzheimer, amyotrophic lateral sclerosis, age macular degeneration, and retinitis pigmentosa [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Although monolayer cultures are relatively easy to be cultivated, the features that they do not display, the complex tissue organization, limits their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cell (iPSC) technologies and patient-derived iPSCs provide opportunities for regenerative medicine, drug discovery, and disease modeling from patient-derived stem cells, such as in cystic fibrosis, Huntington’s, Duchenne muscular dystrophy, Alzheimer, amyotrophic lateral sclerosis, age macular degeneration, and retinitis pigmentosa [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Although monolayer cultures are relatively easy to be cultivated, the features that they do not display, the complex tissue organization, limits their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hPSCs are amenable to genome engineering and provide an opportunity to derive iPSC lines from patients carrying disease-associated mutations, making hPSC-derived organoids particularly well suited for modeling genetic disease. iPSC lines derived from patients have been shown to recapitulate pathologic phenotypes in retinal [108], lung [20,66,78], kidney [21], intestinal [109], and colonic [110,111] organoids, among many others. In many of these studies, genome engineering is applied to generate mutation-corrected iPSC lines, which permit the comparison of organoid development between genetic backgrounds that only differ at the site of the mutation under investigation.…”
Section: Current and Future Applications For Organoidsmentioning
confidence: 99%
“…A similar study used ZFNs to correct Phe508del and demonstrated restored CFTR protein expression and function in air-liquid interface cultures established from the edited basal cells ( Suzuki et al, 2020 ). TALEN technologies have also been used to restore normal CFTR expression and activity in organoids derived from Phe508del patient-derived iPSCs ( Fleischer et al, 2020 ). The ability to achieve CFTR correction in additional stem/progenitor cells such as airway basal cells, either as primary airway basal cells or those derived from iPSCs, has specific relevance for progress toward cell-based therapies for CF.…”
Section: Cell-based Therapiesmentioning
confidence: 99%